Identification of Potent and Selective Inhibitors of the Plasmodium falciparum M18 Aspartyl Aminopeptidase (PfM18AAP) of Human Malaria via High-Throughput Screening. (August 2014) - Spicer, Timothy; Fernandez-Vega, Virneliz; Chase, Peter; Scampavia, Louis; To, Joyce; Dalton, John P.; Da Silva, Fabio L.; Skinner-Adams, Tina S.; Gardiner, Donald L.; Trenholme, Katharine R.; Brown, Christopher L.; Ghosh, Partha; et al.
The target of this study, the Pf M18 aspartyl aminopeptidase ( Pf M18AAP), is the only AAP present in the genome of the malaria parasite Plasmodium falciparum. Pf M18AAP is a metallo-exopeptidase that exclusively cleaves N-terminal acidic amino acids glutamate and aspartate. It is expressed in parasite cytoplasm and may function in concert with other aminopeptidases in protein degradation, of, for example, hemoglobin. Previous antisense knockdown experiments identified a lethal phenotype associated with Pf M18AAP, suggesting that it is a valid target for new antimalaria therapies. To identify inhibitors of Pf M18AAP function, a fluorescence enzymatic assay was developed using recombinant Pf M18AAP enzyme and a fluorogenic peptide substrate (H-Glu-NHMec). This was screened against the Molecular Libraries Probe Production Centers Network collection of ~292, 000 compounds (the Molecular Libraries Small Molecule Repository). A cathepsin L1 (CTSL1) enzyme-based assay was developed and used as a counterscreen to identify compounds with nonspecific activity. Enzymology and phenotypic assays were used to determine mechanism of action and efficacy of selective and potent compounds identified from high-throughput screening. Two structurally related compounds, CID 6852389 and CID 23724194, yielded micromolar potency and were inactive in CTSL1 titration experiments (IC50 >59.6 µM). As measured by the Ki assay, both compounds demonstrated micromolar noncompetitive inhibition in the Pf M18AAP enzyme assay. Both CID 6852389 and CID 23724194 demonstrated potency in malaria growth assays (IC50 4 µM and 1.3 µM, respectively).